(untitled) (REMUNOM, 2023)
Introduction: Since dental procedures can cause pain and therefore fear in patients, several options of anesthetics have been developed for the best effect depending on the patient’s needs. At the same time, the number of patients with systemic diseases has clearly increased over the years, and it has become essential for the dental surgeon to have knowledge about these multiple systemic disorders that go beyond normality, such as hypertension, diabetes mellitus, heart diseases, pregnancy, and others. Objectives: The objective of the present study was to evaluate the knowledge of undergraduate dental students of the Universidade Federal de Campina Grande regarding the use of local anesthetics against systemic conditions. Methodology: The present research is a cross-sectional study, of exploratory type, with a quanti-qualitative approach, in which a questionnaire will be given to undergraduate dental students who have already taken the discipline of anesthesiology. Results: A considerable part of the sample was composed of female undergraduates who belonged to the 6th period, moreover, most of them were seeing patients in the dental school clinic. According to the results presented, only 04 of the 10 questions regarding the use of local anesthetics had correct answers. Conclusion: The present research indicates that undergraduate dental students of the UFCG present a certain deficit of knowledge regarding the use of local anesthetics against systemic conditions. The results presented during the research point to the lack of knowledge and the probability of adverse reactions due to incorrect anesthetic choice.